Including physiological data in a science of behavior: A critical analysis (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
The position of behavior analysts on the inclusion of physiological data in behavior analysis varies. David Schaal, a contemporary behavior analyst, addressed advantages of such inclusion to behavior analysis with four arguments: (a) identification of retention mechanisms of operant conditioning; (b) physiology provides explanations when descriptions are not sufficient; (c) elucidation of cellular and neural mechanisms of reinforcement; and (d) characterization of degenerative alterations in the brain. The present paper provides further discussion of these points as to whether they truly represent an advantage to behavior analysis. It is argued and exemplified that behavior analysis and neuroscience are not mutually exclusive. Finally, the conditions under which the inclusion of physiological data in behavior analysis represents an advantage to the field are delineated.